Patients’ perceived needs for medical services for non-specific low back pain: A systematic scoping review - Chou, L.; Ranger, T.; Peiris, W.; Cicuttini, F.; Urquhart, D.; Sullivan, K.; Seneviwickrama, M.; Briggs, Andrew; Wluka, A. (Public Library of Science, 2018)
Background: An improved understanding of patients’ perceived needs for medical services for low back pain (LBP) will enable healthcare providers to better align service provision with patient expectations, thus improving patient and health care system outcomes. Thus, we aimed to identify the existing literature regarding patients’ perceived needs for medical services for LBP. Methods: A systematic scoping review was performed of publications identified from MEDLINE, EMBASE, CINAHL and PsycINFO (1990–2016). Descriptive data regarding each study, its design and methodology were extracted and risk of bias assessed. Aggregates of patients’ perceived needs for medical services for LBP were categorised. Results: 50 studies (35 qualitative, 14 quantitative and 1 mixed-methods study) from 1829 were relevant. Four areas of perceived need emerged: (1) Patients with LBP sought healthcare from medical practitioners to obtain a diagnosis, receive management options, sickness certification and legitimation for their LBP. However, there was dissatisfaction with the cursory and superficial approach of care. (2) Patients had concerns about pharmacotherapy, with few studies reporting on patients’ preferences for medications. (3) Of the few studies which examined the patients’ perceived need of invasive therapies, these found that patients avoided injections and surgeries (4) Patients desired spinal imaging for diagnostic purposes and legitimation of symptoms. Conclusions: Across many different patient populations with data obtained from a variety of study designs, common themes emerged which highlighted areas of patient dissatisfaction with the medical management of LBP, in particular, the superficial approach to care perceived by patients and concerns regarding pharmacotherapy. Patients perceive unmet needs from medical services, including the need to obtain a diagnosis, the desire for pain control and the preference for spinal imaging. These issues need to be considered in developing approaches for the management of LBP in order to improve patient outcomes.